Pemanfaatan Media Online Sebagai Sumber Bahan Ajar Mata Kuliah Dokkai Sakubun Shokyu - Dwi Puji Asrini; Ai Sumirah Setiawati (KIRYOKU, 2022)
The purpose of learning Dokkai Sakubun, is no longer just being able to read and understand vocabulary, kanji, bunkei, hyogen and also use them in sentences. Along with its development, this course aims to make students able to apply the knowledge gained from reading activities into writing that can be expressed in everyday life. In this digital era, teachers can take advantage of all the information available in cyberspace as a source of teaching materials. This research is a descriptive study with the aim of utilizing online media as a source of teaching materials in the Dokkai Sakubun Shokyu Course and compiling teaching materials with sources from online media. This research method is descriptive qualitative, with data collection techniques in the form of questionnaires and direct observation. Questionnaires were given to determine students' perceptions of the use of teaching language sources from online media in learning Dokkai Sakubun Shokyu. Direct observations were made to strengthen the results of the questionnaire regarding the benefits of media in learning and compiling learning materials. The results showed that online media can be used as a source of teaching materials in the Dokkai Sakubun Shokyu Course. Teaching materials are selected based on predetermined topics in the form of videos sourced from YouTube, leaflets, famlets, brochures, tickets, restaurant menus, conversations in email or chat  and so on, then arranged in the form of handouts.